ETHNOMATHEMATICS: LEARNING GEOMETRY FROM HOK TEK BIO TEMPLE IN PURWOKERTO, INDONESIA - Kusno, Kusno; Setyaningsih, Eka; Gunawan, Gunawan; Kusuma, Jaka Wijaya (Nindikayla Institute, 2025)
Hok Tek Bio Temple in Purwokerto, Central Java, Indonesia as one of the cultural sites rich in symmetrical architectural elements, carved ornaments, and geometric shapes, offers a unique opportunity for students to visualize various types of geometric transformations. However, so far it has not been widely used as a medium in mathematics learning. This study aims to explore Hok Tek Bio Temple in Purwokerto as a medium for mathematics learning through ethnomathematics studies. This study uses a qualitative method with an ethnographic approach. Data collection techniques use in-depth interviews, observations and document studies. The results of the study show that most of the Hok Tek Bio Temple ornaments are built using geometric transformation patterns, both reflection, translation, dilation, and symmetry, which have various philosophical meanings in life. The results of this study can be recommended as a medium for learning geometry based on local wisdom and at the same time character education